Evaluation of cytotoxicity and genotoxicity of a novel oxovanadium complex with orotate - da Silva Gomes, Pietra Stefany; da Silva, Washington Wilson; de Cássia Gasparoti, Gabriela; Payolla, Filipe Boccato; de Oliveira, Jonata Augusto [UNESP]; Barbugli, Paula Aboud [UNESP]; Marin-Dett, Freddy Humberto [UNESP]; Cavicchioli, Maurício; Massabni, Antonio Carlos; Resende, Flávia Aparecida (Elsevier, 2022)
The development of new drugs based on metal complexes requires a detailed analysis of their biological endpoints. In this study, we report the genotoxic profile and influence on cell proliferation and death of the oxovanadium(IV) complex with orotic acid ([VO(C5H4N2O4)2], VO(oro)). Human hepatocellular carcinoma cells (HepG2) were the most sensitive tumor cells to VO(oro), which interfered with the integrity of cell membranes and proliferative capacity in a dose-dependent manner, inducing cell death by apoptosis. Regarding genotoxicity, VO(oro) did not induce considerable levels of DNA damage in HepG2 cells (comet test) and gene mutations (Ames test). However, it caused a statistically significant increase in the frequency of micronuclei at the highest concentration tested (12.5 µmol.L–1), indicating aneuploidy and clastogenicity. The data presented here provide information on various biological aspects of the VO(oro) complex, which may allow the elucidation of its mechanism of action as a possible therapeutic agent.
Keywords: Cytotoxicity; Genomic instability; Mutagenicity; Oxovanadium complex; Toxicogenetics